Patient Dissatisfaction Following Total Knee Arthroplasty: A Systematic Review of the Literature - Gunaratne, Rajitha; Pratt, Dylan N.; Banda, Joseph; Fick, Daniel P.; Khan, Riaz J.K.; Robertson, Brett W. (The Journal of arthroplasty, 2017)
Dissatisfaction following total knee arthroplasty (TKA) is common. Approximately 20% of patients report dissatisfaction following primary TKA. This systematic literature review explores key factors affecting patient dissatisfaction following TKA. Six literature databases published between 2005 and 1 January 2016 were searched using 3 key search phrases. Papers were included if the study investigated patient dissatisfaction in primary unilateral or bilateral TKA. Information from each article was categorized to the domains of socioeconomic, preoperative, intraoperative, and postoperative factors affecting patient dissatisfaction. This review found that patient dissatisfaction pertains to several key factors. Patient expectations prior to surgery, the degree of improvement in knee function, and pain relief following surgery were commonly cited in the literature. Fewer associations were found in the socioeconomic and surgical domains. Identifying who may be dissatisfied after their TKA is mystifying; however, we note several strategies that target factors whereby an association exists. Further research is needed to better quantify dissatisfaction, so that the causal links underpinning dissatisfaction can be more fully appreciated and strategies employed to target them.